2020
DOI: 10.3390/ph14010001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide K11 Selectively Recognizes Bacterial Biomimetic Membranes and Acts by Twisting Their Bilayers

Abstract: K11 is a synthetic peptide originating from the introduction of a lysine residue in position 11 within the sequence of a rationally designed antibacterial scaffold. Despite its remarkable antibacterial properties towards many ESKAPE bacteria and its optimal therapeutic index (320), a detailed description of its mechanism of action is missing. As most antimicrobial peptides act by destabilizing the membranes of the target organisms, we investigated the interaction of K11 with biomimetic membranes of various pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 128 publications
1
8
0
Order By: Relevance
“…Micelles allow the study in solution and provide a very rough model of the apolar environment within biological membranes. Contrary to other peptides [79,80] and despite the complementary charges of the exposed choline groups, Sesquin does not seem to interact with DPC micelles (Figure S2), suggesting its poor affinity for the hydrophobic environment found in bilayers and the absence of a specific recognition of PC headgroups. Isotropic bicelles and liposomes are more realistic models, allowing to evaluate the interactions with a wider variety of phospholipids, able to better reproduce the membranes of different organisms [62,81].…”
Section: Studies With Dpc Micelles Suggests Poor Affinity For Pc Head...mentioning
confidence: 84%
“…Micelles allow the study in solution and provide a very rough model of the apolar environment within biological membranes. Contrary to other peptides [79,80] and despite the complementary charges of the exposed choline groups, Sesquin does not seem to interact with DPC micelles (Figure S2), suggesting its poor affinity for the hydrophobic environment found in bilayers and the absence of a specific recognition of PC headgroups. Isotropic bicelles and liposomes are more realistic models, allowing to evaluate the interactions with a wider variety of phospholipids, able to better reproduce the membranes of different organisms [62,81].…”
Section: Studies With Dpc Micelles Suggests Poor Affinity For Pc Head...mentioning
confidence: 84%
“…A recent ample analysis highlighted the antimicrobial peptides' characteristics that interact with bacterial membranes [ 38 , 39 ]. The assessment of the portion of the fatty acids, compared to the sensitivity rate of the antibiotics used in present study, was higher in phenotype S, compared to phenotype R, a fact also found by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The in-plane topology is probably stabilized by the negative surface charge density and the additional hydrogen bonding possibilities of the PG bilayers that favorably interact with the histidines (and lysines). Indeed, molecular dynamics calculations show an accumulation of close contacts between cationic amino acids of membrane-inserted antimicrobial peptides and the PG phosphate groups [64,65]. Furthermore, due to the negative surface charge density of the PG bilayer there is a pH gradient between the bulk and the membrane surface during the sample preparation which may persist even in the reduced volume of the stacked membranes (Fig.…”
Section: The Ip To Tm Transition In Popgmentioning
confidence: 99%